2012
DOI: 10.7860/jcdr/2012/4197.2564
|View full text |Cite
|
Sign up to set email alerts
|

Blue Rubber-Bleb Nevus Syndrome which was Associated with an Atrial Septal Defect: A Case Report

Abstract: The Blue Rubber Bleb Nevus Syndrome (BRBNS) is a rare cause of persisting gastrointestinal bleeding. We are presenting a case which was associated with an atrial septal defect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Rarely, complications like intussusception, volvulus, infarction or hemorrhage can occur. There are few reports of BRBNS with associated cardiac defects like atrial and ventricular septal defects and pulmonary hypertension secondary to thromboembolic events [5,6]. Our patient had pulmonary stenosis, an association hitherto undescribed.…”
Section: Discussionmentioning
confidence: 80%
“…Rarely, complications like intussusception, volvulus, infarction or hemorrhage can occur. There are few reports of BRBNS with associated cardiac defects like atrial and ventricular septal defects and pulmonary hypertension secondary to thromboembolic events [5,6]. Our patient had pulmonary stenosis, an association hitherto undescribed.…”
Section: Discussionmentioning
confidence: 80%
“…In addition, previous studies have shown some very uncommonly involved tissues. For example, Aroor et al described a case of BRBNS with an atrial septal defect [3]. Huang et al reported a case of BRBNS with both GI and central nervous system involvement.…”
Section: Discussionmentioning
confidence: 99%
“…The management of BRBNS remains considerably challenging, and the lesions in the skin rarely bleed. In contrast, GI lesions manifest throughout the GI tract and begin to bleed at an early age, persisting for the rest of a person's life [3]. The treatment plan is dependent on the extent of the GI involvement and severity of the clinical condition.…”
Section: Discussionmentioning
confidence: 99%